Pengaruh Strategi Pailkem terhadap Peningkatan Prestasi Belajar Siswa - Wildana, Wildana (JURNAL AL-QAYYIMAH, 2018)
This article discusses the influence of active learning strategies, innovative environment, creative, effective and interesting in improving learning achievements of students, PAI this strategy is a form of strategy that can arouse the interest of students in learning follow the learning activities because this strategy is a form of strategy that can encourage students to be more active in creative and innovative learning activities and environmental dimamfaatkan as a source of learning. So that students are more motivated in learning activity. In a study using PAILKEM strategies (learning, active, innovative, effective, creative, environment, interesting), an interactive dialogue will take place between students with students, students with teachers or students with other learning resources . In a study like this, students are not burdened in an individual in solving problems encountered in the study. So it will grow and develop all the potential they possess so that in the end can optimize their learning outcomes.